2023
DOI: 10.3389/fphar.2023.1147823
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of cyclophosphamide-induced DNA damage, oxidative stress, and hepato- and neurotoxicity by Piper longum extract in rats: The role of γH2AX and 8-OHdG

Abstract: Background: The identification of genoprotectants is a promising strategy for improving human health. Piper longum has drawn scientific attention because of its diverse biological effects and traditional utilization. The current investigation aims to evaluate the genome-stabilizing potential of Piper longum against cyclophosphamide-associated genotoxicity.Methods: We adopted a funnel screening with a three-tier evaluation approach, where Piper longum was investigated in an acellular medium, peripheral blood ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…As higher flufiprole metabolite concentrations were detected at 35 °C than that at 15 or 25 °C, it can be predicted that the more serious liver lesions in the higher-temperature group were induced by the flufiprole oxidative reaction during metabolism. The inflammation in the liver caused by flufiprole may have a protective effect on the liver . All these lesions, including inflammatory cell infiltration and porphyrin pigment deposition, were also highly related to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As higher flufiprole metabolite concentrations were detected at 35 °C than that at 15 or 25 °C, it can be predicted that the more serious liver lesions in the higher-temperature group were induced by the flufiprole oxidative reaction during metabolism. The inflammation in the liver caused by flufiprole may have a protective effect on the liver . All these lesions, including inflammatory cell infiltration and porphyrin pigment deposition, were also highly related to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The inflammation in the liver caused by flufiprole may have a protective effect on the liver. 54 All these lesions, including inflammatory cell infiltration and porphyrin pigment deposition, were also highly related to oxidative stress. The oxidative DNA damage induced by diazinon also showed serious inflammation in rabbit liver.…”
Section: Liver Lesions Induced By Flufiprolementioning
confidence: 99%
“…8-OHdG and γH2AX are critical biomarkers of DNA damage [ 17 ]. AU565 cells were stimulated with Neratinib (1, 2.5, and 5 μM) for 72 h. The 8-OHdG ( Figure 3A ) and γH2AX ( Figure 3B ) levels in AU565 cells were remarkably elevated as the concentration of Neratinib increased from 1 to 5 μM, implying a facilitating effect of Neratinib on DNA damage in AU565 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various studies demonstrated that oxidative stress elicited by cyclophosphamide in the brain is mediated through overproduction of reactive oxygen species (ROS), GSH depletion and inhibition of antioxidant enzymes activities [13,14]. In addition, it was found that the activation of angiotensin converting enzyme and the resultant excessive production of angiotensin II by cyclophosphamide has been implicated in ROS generation and hence the subsequent oxidative brain injury [15].The massive generation of ROS prompts oxidative damage to numerous cellular components resulting in lipid peroxidation, DNA damage and mitochondrial dysfunction [14,[16][17][18]. Mechanisms by which cyclophosphamide-induced oxidative stress is shown in Fig.…”
Section: Induction Of Oxidative Stressmentioning
confidence: 99%
“…Notably, nerolidol has exhibited worthy neuroprotective activity [87,88]. Iqbual et al [18] has examined the effect of nerolidol on cyclophosphamide-induced chemobrain. In this study, mice were given nerolidol orally at doses of 200 or 400 mg/kg for 14 days then cyclophosphamide (200 mg/ kg i.p.)…”
Section: Nerolidolmentioning
confidence: 99%